The dynamics and demography of socially structured carnivores - Massey, J (2015)
Sociality in carnivores is theoretically expected to produce quantitatively different dynamics compared to solitary species, exhibiting Allee effects, increasing extinction risk and limiting population growth. There is also evidence in social species that demographic stochasticity can impact the population when densities are high. Empirical support for these processes is lacking and the effects of socio-spatial structure on population dynamics is now widely debated. The roles of social structure, reproductive suppression, communal predator vigilance, communal hunting and babysitting on population responses to perturbations away from carrying capacity have important implications for species management. Social systems also possess inherent spatial structure. Such structure is known to influence dynamics in solitary species. This thesis investigates the relative contributions of spatial and social structure on population dynamics in three contrasting carnivores, from three different families; badgers (Meles meles), lions (Panthera leo) and grey wolves (Canis lupus), that each demonstrate comparable and different life history strategies with one another. Simple and complex structured population models are used to demonstrate how intra-group processes interact within inter-group process and habitat features to produce population wide dynamics. The models are used to investigate whether general rules governing the dynamics of social species can be drawn across species.